2012
DOI: 10.1007/s10856-012-4651-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled polymeric nanoparticles based on oleic acid-grafted chitosan oligosaccharide: biocompatibility, protein adsorption and cellular uptake

Abstract: Oleic acid-grafted chitosan oligosaccharide (OA-g-CSO) was synthesized to prepare self-assembled nanoparticles by sonication at physiological pH value (7.4). The nanoparticles appeared to be spherical in shape with a diameter of 158.1 ± 64.3 nm. The biocompatibility of OA-g-CSO nanoparticles was evaluated in vitro via MTT assay and hemolysis test. The nanoparticles showed no cytotoxicity to mouse embryo fibroblasts and the hemolysis rates came well within permissible limits (<2 %) in the tested conditions. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…One phenomenon easy to find in many cell lines is the reduction in the ability to produce formazan deposits even when NPs are incubated at a sublethal dose. [69][70][71] This result is intended as an index of mitochondrial stress, since the reaction involved in the formazan formation is catalyzed by a mitochondrial reductase. It has been demonstrated that a perturbation of the normal mitochondrial activity is correlated with an increase in reactive oxygen species (ROS) production.…”
Section: Effects Of Nanoparticles On Cellular Physiologymentioning
confidence: 99%
“…One phenomenon easy to find in many cell lines is the reduction in the ability to produce formazan deposits even when NPs are incubated at a sublethal dose. [69][70][71] This result is intended as an index of mitochondrial stress, since the reaction involved in the formazan formation is catalyzed by a mitochondrial reductase. It has been demonstrated that a perturbation of the normal mitochondrial activity is correlated with an increase in reactive oxygen species (ROS) production.…”
Section: Effects Of Nanoparticles On Cellular Physiologymentioning
confidence: 99%
“…This also suggests that altering or manipulating the surface chemistry will aid in increased or decreased uptake of nanoparticles by the cells and also increases the circulation time in blood [55,57]. Adsorption of plasma proteins on nanoparticles enhances its stability by reducing agglomeration, drug carrier efficiency and also increases its compatibility with the biological system [35,58]. Thus our results indicate that LaNRs are biocompatible as revealed through BSA adsorption and can be efficiently used for therapeutic purposes.…”
Section: Protein Adsorptionmentioning
confidence: 59%
“…Particles were then washed to remove excess BSA by centrifugation at 14,000 rpm for 15 min. The protein was desorbed from the surface of LaNRs by sonication in the presence of PBS containing 1 % SDS [35]. The samples were subjected to 10 % SDS-PAGE [36] and stained with Coomassie Brilliant Blue R-250 (Merck, India).…”
Section: Protein Adsorption Studymentioning
confidence: 99%
“…Previously, Zhang et al . illustrated the development of oleic acid grafted chitosan oligosaccharide and used as drug carrier, however, did not discuss about the micellization behavior . Li et al .…”
Section: Introductionmentioning
confidence: 99%